Measurement and political economy of disputed technical regulations - Thornsbury, Suzanne; Roberts, Donna H.; Orden, David (Cambridge University Press, 2004)
Technical regulations are increasingly visible in agricultural trade, yet their idiosyncratic nature has limited prior aggregate analysis. This research draws upon a unique data source for systematic enumeration of the technical regulations questioned by one exporter among all of its trading partners in mid-1996. Political economy analysis indicates that barriers decrease when the relative contribution of agriculture to an economy increases, when the anticipated future level of protection through other forms of government intervention increases, and when economies are more open. Despite increased scrutiny and discipline by the World Trade Organization, technical barriers remain a significant impediment in world agricultural markets.